Penyuluhan Hukum Program Desa Bersih Narkoba di Desa Mancagar, Kuningan - Muhamad Yaqutatul Hadro; Aan Triwijayanto; Imas Masyitoh; Siti Mauliya Kusumah; Fajar Sidik; Sandi Lesmana; Erga Yuhandra (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
A growing perspective in society concerns the high costs of handling legal proceedings. This mindset influences actions, especially among the underprivileged. Therefore, when facing legal issues, they are reluctant to pursue the court process and simply accept the unfair treatment without doing anything. They don't know where else to fight for their rights. In other situations, unfair treatment is met with violence, resulting in them becoming victims. Ultimately, access to justice is deemed inaccessible to the lower classes. Article 28D paragraph (1) of the 1945 Constitution states that everyone has the right to recognition, guarantees, protection, and certainty of fair law, as well as equal treatment before the law. Therefore, the Kuningan University Legal Aid Center has gone out into the community to provide counseling on every legal issue faced by the people of Mancagar Village, along with training on the P4GN program, in order to create a Shining Village. Drug crimes are considered extraordinary crimes, requiring extraordinary efforts to eradicate them. Drug abuse, the majority of whom are young people (those of productive age), has reached a very alarming level.